THE INFLUENCE OF SOCIAL MEDIA MARKETING AND BRAND IMAGE TOWARDS CUSTOMER’S PURCHASE DECISION AT FISH & CO. CENTRE POINT MEDAN - Arabella; Alfonsius (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2022)
Fish & Co. located at Centre Point Medan is a seafood restaurants, a part of Bisa Group, being famous with its tagline “Best Fish & Chips in Town”, have implemented the social media marketing activities in its Instagram page. However, Fish & Co. have faced a decreasing in the number of orders, where many of the customers only purchase Fish & Co. during promotions, less interaction in its social media, and less reviews on Fish & Co. foods. This research aims to find out whether there is an influence from social media marketing and brand image towards customer’s purchase decision. This research use quantitative research, which by distributing questionnaires to 100 of respondents who have ever purchased at Fish & Co. Centre Point Medan in last 2 years. This research also use multiple linear regression by using the SPSS application v. 26 to analyze the data. The result of this research shows that the social media marketing and brand image simultaneously influence the customer’s purchase decision at Fish & Co. Centre Point Medan by 69%. The social media marketing partially influence the customer’s purchase decision at Fish & Co. Centre Point Medan by 31% . In addition, the brand image have the most significant, with 83% influence on the customer’s purchase decision at Fish & Co. Centre Point Medan.